2022
DOI: 10.1155/2022/5254823
|View full text |Cite
|
Sign up to set email alerts
|

Research on Painting Image Classification Based on Transfer Learning and Feature Fusion

Abstract: In order to effectively solve the problems of high error rate, long time consuming, and low accuracy of feature extraction in current painting image classification methods, a painting image classification method based on transfer learning and feature fusion was proposed. The global characteristics of the painting picture, such as color, texture, and form, are extracted. The SIFT method is used to extract the painting’s local features, and the global and local characteristics are normalized and merged. The pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…When we compare our results to those of other relevant research, we find that our model's performance is on par with or better than that of earlier efforts in garbage categorization. For example, Thung and Yang reached an 87% accuracy using a ResNet-50 and SVM technique [1], while another study utilizing a unique trash image recognition model revealed a high recall rate and accuracy [2]. Furthermore, our model outperformed other techniques, including Xception_CutLayer and InceptionResNetV2_CutLayer, which had accuracies of 89.72% and 85.77%, respectively [3].…”
Section: Vdiscussionmentioning
confidence: 78%
See 3 more Smart Citations
“…When we compare our results to those of other relevant research, we find that our model's performance is on par with or better than that of earlier efforts in garbage categorization. For example, Thung and Yang reached an 87% accuracy using a ResNet-50 and SVM technique [1], while another study utilizing a unique trash image recognition model revealed a high recall rate and accuracy [2]. Furthermore, our model outperformed other techniques, including Xception_CutLayer and InceptionResNetV2_CutLayer, which had accuracies of 89.72% and 85.77%, respectively [3].…”
Section: Vdiscussionmentioning
confidence: 78%
“…The dataset has been expanded through data augmentation; the resulting dataset contains 41,650 garbage images. The results of the experiments demonstrate that the suggested model has good convergence, a high recall rate and accuracy, and a short recognition time when compared to other models [2]. Six distinct waste materials were used in the training and testing of the suggested techniques and AI-based deep learning techniques.…”
Section: Figure 1 Solid Waste Management Illustrationmentioning
confidence: 97%
See 2 more Smart Citations
“…With the development of contemporary painting, modern landscape art pays more attention to fun. Sex and aesthetics, this change is also inseparable from the development of painting art [14].…”
Section: The In Uence Of Modern Extracurricular Painting On Landscape...mentioning
confidence: 99%